Three Cs of Translating Evidence‐Based Programs for Youth and Families to Practice Settings. Issue 149 (September 2015) - Freire, Kimberley E.; Perkinson, Leah; Morrel‐Samuels, Susan; Zimmerman, Marc A.
Abstract: Despite the growing number of evidence‐based programs (EBPs) for youth and families, few are well‐integrated in service systems or widely adopted by communities. One set of challenges to widespread adoption of EBPs relates to the transfer of programs from research and development to practice settings. This is often because program developers have limited guidance on how to prepare their programs for broad dissemination in practice settings. We describe Three Cs of Translation, which are key areas that are essential for developers to translate their EBPs from research to practice settings: (1) Communicate the underlying theory in terms easily understandable to end users, (2) Clarify fidelity and flexibility, and (3) Codify implementation lessons and examples. Program developers are in the best position to describe their interventions, to define intervention core components, to clarify fidelity and flexibility, and to codify implementation lessons from intervention studies. We note several advantages for developers to apply the Three Cs prior to intervention dissemination and provide specific recommendations for translation. © 2015 Wiley Periodicals, Inc.